Consumption, motivation and experience in dark tourism: a conceptual and critical analysis - Iliev, Dejan (Informa UK Limited, 2020)
A review of recent relevant literature related to dark tourism indicates that there is a growing academic interest in ‘dark tourism consumption’, ‘dark tourism motivation’ and ‘dark tourism experience’. Therefore, the objectives of the present research are threefold: to examine the progress of research on these three concepts; to give a critical analysis of recent research; and to identify research gaps and questions that require fuller examination. In order to adopt new research orientations, the use of a broader post-disciplinary research framework is in need. The findings reveal that the three concepts are evolving and advancing, and new researches push the boundaries of exploration into new directions. From the analysis of recent literature, it can be concluded that thanatopsis is a rare characteristic of tourist visits. This is in contrast to the early conceptual studies, which claim that death is the primary motive for visiting dark sites. The findings reveal that many visitors are motivated by the desire and an interest in cultural heritage, learning, education, understanding about what happened at the dark site etc. It is important to emphasise that these motivations are affected by internal conflicts that the experience generates. Tourist experience is more in line with that of а mainstream heritage sites. In general, if tourists do not experience a site as dark, then they cannot be called dark tourists. Hence, the present research appeals to a clearer distinction of the ‘dark tourists’ based on experience. Except for the ‘mortality mediation model’, ‘dystopian dark tourism’ and ‘Terror Management Theory’, there are limit efforts to understand tourists at dark sites. Therefore, scientists must propose new approaches and additional empirical researches to prove that interest in death is a key motive for visiting dark sites. Lastly, from the literature review, new directions for further research have emerged.
Keywords: Concept, consumption, critical insights, dark tourism, experience, motivation